PERAN GURU DALAM PEMBENTUKAN KARAKTER DISPLIN - Rahmad Ilahi; Muhammad Nazir Putra; Abdul Munip; Mawardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
The character of discipline is one of the most important characters for every student to have. Therefore, the teacher must carry out his role in shaping the character of student discipline. This study aims to analyze the teacher's role in the formation of disciplinary character. This study uses a qualitative approach to the type of field research. The subjects of this study were class teachers who were determined by purposive sampling technique. The data collection technique used is to explain what roles are played by the teacher in shaping the disciplinary character of students in the new normal era. In addition, the results of the research also show that there are several inhibiting factors in the formation of disciplinary character.